Psychometric properties of the Persian version of the electroconvulsive related anxiety questionnaire for psychiatric patients - EghbalManesh, Azadeh; Ebadi, Abbas; Zoladl, Mohammad; Rasoul Zadeh Haghighi, Zahra (Frontiers in Psychology, 2025)
IntroductionECT is one of the most effective treatments for psychiatric patients. The results of several studies have reported ECT-related anxiety, which makes the patients ignore the advantages of the treatment and subsequently avoid it. Adopting an appropriate instrument to evaluate and manage this anxiety is so significant. Since there is no valid questionnaire to assess the patients' anxiety for ECT in Persian, we aimed to translate the EARQ into Persian and evaluate its validity and reliability in the present study.MethodsIn this methodological study, 170 patients with MDD, BMD, and schizophrenia aged 20–73 were recruited through convenience sampling and completed the 17-item EARQ in 2023. We used all aspects of face, content, and construct validity for the questionnaire. McDonald's Omega was calculated for the domains and 17 items to assess the reliability of the questionnaire.ResultsExploratory and confirmatory factor analysis revealed three factors, death anxiety, physical concern, and mental concern. Confirmatory factor analysis indicated moderate fit indices to support the three domains: CMIN/DF = 4.8 (p < 0/05), RMSEA = 0.152, CFI = 0.92, and NFI = 0.91; GFI = 0.72. In our study, McDonald's Omega was 0.965 for death anxiety, 0.91 for physical concerns, 0.964 for brain concerns, and a total of 0.98.ConclusionsThe EARQ has acceptable validity and reliability, so specialists can use it to assess patients' anxiety before ECT and, according to the score, use suitable interventions to eliminate it.